Prioritizing Educational Policy from Nasa Results: Meta-Analysis of All Nasa Reports from 2011 to 2022 - Acharya, Shyam Prasad (Education Review Journal, 2024)
This article aims to provide insights on how to set priorities in education policies with the NASA results from the equity perspective. I have tried to extract a few examples of NASA results and analyzed the strengths of different variables to show how those variables have influenced in student learning and why those variables are important from the policy formulation point of view. Meta-analysis does not limit on a single year and subject, rather it is extended over years and subjects in the specific areas. From the analysis, it is revealed that provincial differences and mother education are the upcoming focus in educational priorities. There are other important variables pointed out that has to be snatched from this article.